The Role of Digitalization Technologies in Training Specialists in the Field of Medicine (KIUT Publication, 2025)
As the main materials, current experiences related to digitalization in medical universities of Uzbekistan and foreign countries, scientific articles, data published by international health organizations, as well as analyses of online educational platforms such as Medcram, Osmosis, and Kenhub were used. The differences between traditional and digital forms of education, the advantages of modern technologies, and their role and impact in the educational process were analyzed.